18+ years of Brazilian Symposium on Information Systems: Results of a Scope Review - Neves, Vânia; Melo, Silvana; Garcés, Lina (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2023: Anais do XIX Simpósio Brasileiro de Sistemas de Informação, 2023)
Context: The Information Systems community in Brazil, specifically its main national event, the SBSI, has gained prominence in recent years on both the national and international scene. Problem: In 2016, the IS community established a list of the main challenges to be fulfilled by 2026, making it necessary to monitor its evolution. Solution: To provide an overview of research published in the main Brazilian national event of the Information Systems community - the SBSI. A broad analysis of the SBSI's body of knowledge (995 studies), divided into 18 editions, could guide future actions for the IS community. IS Theory: This study is based on argumentative theory to offer the intended overview of the SI area. Method: A scope review was conducted seeking to obtain an overview of primary studies in the IS area, categorizing the research by time, origin, topics, authors’ profiles, industry participation, internationalization, gender inclusion, and status to combat the challenges in IS. Summarization of Results: Among the main results found, we can highlight that female participation is lower compared to male involvement; however, female participation in papers with more significant influence is similar to male involvement; SBSI's research is centered on public and national academic institutions with greater participation in the states of the Brazilian South and Southeast; researchers had worked on IS Grand Research Challenges, however topics related to artificial intelligence have gained prominence in recent years. Contributions and Impacts on the IS area: These results can aid the IS community in reflecting and understanding the current directions of IS research and whether IS challenges can be overcome in the coming years.